Fishmeal supplementation to high producing Jersey cows grazing ryegrass or kikuyu pasture - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2013)
Dissertation (MSc(Agric) (Animal Science))--University of Pretoria, 2008.